Strategic vision of internal communication in municipal organisations – case study - Loureiro, Marlene (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In modern society, communication is a sine qua non condition for the success of or-ganisations and internal communication plays a fundamental role in organisation-al effectiveness. In municipalities, which are also organisations, communication is fundamental and should therefore be valued, particularly internal communication. In this sense, this research explores the importance of internal communication in municipal organisations. Thus, it was defined as the objectives were: to character-ise the internal public of the organisation; to identify the communication flows; to characterise how communication flows; to identify and analyse the existing inter-nal communication tools; to identify the positive and negative aspects of internal communication; to evaluate how internal communication works and to contribute to the increase in studies in the area of organizational communication.